PENINGKATAN PENGETAHUAN STRATEGI BISNIS, AKUNTANSI PERPAJAKAN, DAN ATURAN HUKUM PADA BUMDES WARGA KERTA BAKTI PEKEN - I Wayan Kartika Jaya Utama; Ida Bagus Gde Indra Wedhana Purba; I Ketut Selamet; I Kadek Angga Aditya Mahendra Putra; I Kadek Dwi Marta Dana Putra; Cokorda, Krisna Yudha (Universitas Kadiri, 2024)
Good financial management and compliance with tax regulations are important factors in the sustainability and development of Village-Owned Enterprises (BUMDes). This community service program aims to improve the knowledge of BUMDes Warga Kerta Bakti Peken administrators in the fields of business strategy, tax accounting, and legal regulations. Through intensive training and mentoring, this program has succeeded in improving the competence of administrators in preparing financial reports, filling out tax returns, as well as business strategy and risk management. The results of the activities show a significant increase in understanding and ability, as well as the potential for sustainable BUMDes business development.